Performance analysis of an SMA negative-stiffness double-concave friction pendulum bearing in reinforced concrete frame structure - Shipeng Feng; Ziquan Yang; Liang Wang; Shanchun Fu; Jun Peng; Pengfei Li; Hang Zhao (Soil Dynamics and Earthquake Engineering, 2026)

Multi-environmental biodegradation of a cellulose-based/polylactic acid non-leaching antibacterial composite membrane - Xianpei Xu; Hongbo Wang; Junming Liang; Youbo Di; Mei Liu; Fu Li; Pengfei Fei (Biomass and Bioenergy, 2026)

Reciprocating swing threshing principle for low-damage maize kernel separation: mechanism and experimental validation - Pengfei Hou; Deyi Zhou; Jinsong Zhang; Chengyu Zhang; Jun Fu (Biosystems Engineering, 2026)

Comprehensive assessment of soil health in typical pear orchards in Northwest China - Hongyu Yu; Zhibing Zheng; Bingyue Yu; Xin Wang; Ze Yuan; Kuan Xu; Chen Fu; Tianchi Jiang; Jiapan Lian; Pengfei Liu; Binggan Lou; Wolde tefera; et al. (Soil and Tillage Research, 2026)

The local mediation of rural cultural governance: Problematization, asymmetry, and displaced agency in China's rural cultural revitalization - Pengfei Fu; Ying Zhang; Tong Wu; David Sarpong; George Ofosu (Journal of Rural Studies, 2026)

Outpacing self-trapping: Schottky junction–mediated hot-electron extraction for enhanced photocatalysis - Siyi Zhang; Shiwen Du; Shilong Suo; Zhenfei Fu; Ziyue Zhang; Ni Hu; Zhenhua Zhang; Zhihong Lu; Pengfei Fang (Chemical Engineering Journal, 2026)

Dual repression of OsSnRK1β1A by the deubiquitinase OsOTUB1 orchestrates energy metabolism and grain yield in rice - Ludan Zhang; Pengfei Wang; Yue Li; Shuang Yang; Yan Chen; Zhiying Ma; Jing Pan; Xiaoyu Wang; Chenyan Wang; Haoyuan An; Yuqing Xu; Yifei Xiao; et al. (Molecular Plant, 2026)

Inhibition and metabolic toxicity regulation of niacin on Staphylococcus aureus and its application in meat product preservation - Lei Tian; Xiangqi Bai; Chunyang Huang; Min Li; Ting Zhou; Chunling Zhang; Ying Yu; Hu Pan; Yanna Dai; Jifeng Pu; Chengyu Fu; Pengfei Zhang; et al. (International Journal of Food Microbiology, 2026)

Synergistic organic amendments show broad potential for context-specific regulation of soil available iron in croplands - Hongyu Yu; Bingyue Yu; Erxu Xue; Chen Fu; Jing Chen; Ruiqi Yao; Pengfei Liu; Binggan Lou; Qingxu Ma; Li Chen; Kuan Xu; Jiuzhou Chen; et al. (Applied Soil Ecology, 2026)

Trajectory data–driven modeling and optimization of urban freight charging networks - Yanchao Lu; Runsheng Zhang; Ruoxuan Wang; Bochen Fu; Kaiming Lu; Pengfei Fan; Lei Yu; Guohua Song (Transportation Research Part D: Transport and Environment, 2026)

The effect of hydrothermal desulfation of Gracilaria on the physicochemical and structural alterations of gel by different temperatures - Yunshuang Jiao; Weijie Qiu; Baoshang Fu; Pengfei Jiang; Libo Qi; Shan Shang (Food Chemistry, 2026)

A damage constitutive model for brittle rock considering compaction effect and energy dissipation characteristics - Jiale Fu; Shu Jiang; Linhao Zhang; Pengfei Xiong; Hongji Liu; Ruyang Yu; Zhiping Zhang (Computers and Geotechnics, 2026)

Oriented hetero-phase engineering modulates spontaneous polarization and band alignment - Yumin Wang; Zhenfei Fu; Zewei Zheng; Cheng Gao; Suiting Ning; Yun Tang; Wei Zeng; Pengfei Fang; Yi Xiong (Chemical Engineering Journal, 2026)

SREBP1-activated lipid metabolism drives ferroptosis and progression of clear cell renal cell carcinoma - Bao Wang; Junpeng Fu; Jian Qian; Yuang Wei; Meiling Bao; Haoqi Miao; Xinzhe Zhao; Kezheng Shao; Yuan Song; Ruoyun Tan; Jie Li; Pengfei Shao (Science China Life Sciences, 2026)

Bibliometric and visual analysis of wasp research progress based on ITGInsight - Fu Liu; Jianfang Yang; Jing Huang; Xi Liu; Zizhong Yang; Hairong Zhao; Yu Zhao; Pengfei Gao; Weihong Liu; Chenggui Zhang (International Journal of Tropical Insect Science, 2026)

Test and analysis of soil Microscopic parameters on maize seed displacement and Post-Impact behavior based on a vertical Dual-Camera high-speed imaging system - Xian Jia; Pengfei Zhao; Xiaojun Gao; Zuoli Fu; Gang Guo; Shilin Zhang; Jianxin Dong; Yiming Zhao; Youming Yang; Yuxiang Huang (Computers and Electronics in Agriculture, 2026)

Effects of different thawing methods on the physicochemical and structural properties of frozen quinoa dough - Mengqi Jiao; Yingnan Liu; Baoshang Fu; Pengfei Jiang; Chengrong Wen; Libo Qi; Shan Shang (Journal of Cereal Science, 2026)

Tricomponent synergistic ultrafast photochromism of pyromelliticdiimide-polyoxometalate hybrids for information encryption and smart windows - Xiaojuan Zhang; Jianyu Hao; Shimin Zhang; Shuting Yuan; Minxia Gao; Pengfei Hao; Junju Shen; Yunlong Fu (Chemical Engineering Journal, 2026)

Interaction mechanisms of seed suction and cleaning negative pressure of an air-suction seed metering device for maize breeding plots - Pengfei Zhao; Qingbin Song; Yubin Bi; Jianxin Dong; Zuoli Fu; Yuxiang Huang; Yi Zheng (Biosystems Engineering, 2026)

Molecular crystal memristor-based edge AI platform for energy-efficient and real-time smart grid inspection - Pengfei Guan; Lanhao Qin; Ke Ning; Jie Liu; Decai Ouyang; Yimeng Yu; Jinsong Wu; Xing Lu; Yingshuang Fu; Yuan Li; Huiqiao Li; Tianyou Zhai (Science Bulletin, 2026)

Insights into land deformation processes in the Yellow River Delta (China) from synthetic aperture radar interferometry time series and machine learning - Pengfei Ge; Mi Chen; Roberto Tomás; Hui Liu; Kailun Fan; Xi Cheng; Xingyuan Fu; Shuang Wang (Advances in Space Research, 2026)

Correction–fusion of NWP precipitation conditioned by rainfall stations and multivariate environmental information - Qingzhi Zhao; Pengfei Geng; Zufeng Li; Yibin Yao; Yatong Li; Xiaohua Fu; Qiong Wu (Advances in Space Research, 2026)

Preparation of amidoxime-functionalized titanium carbide and investigation of its adsorption behavior and mechanism for U(VI) - Liming Fu; Zhongchao Wang; Chao Zhou; Pengfei Yang; Guowen Peng (Process Safety and Environmental Protection, 2026)

Enhanced CO2 desorption from monoethanolamine solution using TiO(OH)2-modified diatomite catalyst - Pan Zhang; Zhongfa Zha; Jiawen Yang; Xinbo Wang; Jianwen Song; Shuming Du; Liwen Li; Kun Zhao; Dong Fu; Lemeng Wang; Jun Ke; Pengfei Qu (Process Safety and Environmental Protection, 2026)

Fungal communities dominate accumulation of microbial necromass carbon after 11-year revegetation in a semi-arid desert mining area - Pengfei Li; Wenjiang Fu; Yiwei Bai; Daren Zhou; Shiqi Sun; Qiao Guo; Jianguo Zhang; YanPing Miao; Hangxian Lai (Journal of Environmental Management, 2026)

Antibacterial mechanism of vitamin C against Staphylococcus aureus, reduction of toxicity of metabolites and its application in pasteurized milk - Lei Tian; Chunyang Huang; Xing Liu; Yuxin Zhang; Ting Zhou; Ying Yu; Chunling Zhang; Hu Pan; Yanna Dai; Jifeng Pu; Chengyu Fu; Pengfei Zhang; et al. (International Journal of Food Microbiology, 2026)

Fuel stratification effects on flame dynamics and combustion instability for strongly coupled stratified flames - Pengfei Fu; Jiacheng Lyu; Jinxiang Zhu; Shan Li; Tengyu Liu; Zhenhai Wang; Zhixin Zhu; Gaofeng Wang (Fuel, 2026)

Thermal polymerization and structural analysis of ovotransferrin fibrils: Antibacterial activity and mechanism of action - Xianjiang Ye; Wei Hu; Xi Zeng; Pengfei Geng; Yixin Zhang; Jihan Mohamed Kassem; Xing Fu (Food Research International, 2026)

Fe-N4 single-atom nitrogen doped carbon catalyst: Dual-functional design for PMS-activated antibiotic degradation and efficient oxygen reduction reaction - Yamin Yang; Limeng Yang; Qi Zhang; Yaru Li; Longsheng Cao; Qingshan Li; Chengyu Fu; Cuihong Sheng; Siyuan Zhang; Haijiao Xie; Pengfei Zhang (Chemical Engineering Journal, 2026)

Effects of radio frequency explosion puffing on the texture of purple sweet potato chips and structural properties of pectin under different energy inputs and pressures - Chao Mao; Zhi Chang; Shijing Zhang; Pengfei Ye; Lei Yuan; Xiangwei Chen; Yequn Wang; Hongfei Fu; Yunyang Wang; Ke Wang (Food Research International, 2025)

Comparative analysis of flavour profiles in cooking liquids from razor clams (Solen grandis) processed by different methods - Yujun Liu; Long Li; Di Yu; Pengfei Jiang; Xinrui Yang; Zhiyu Fu; Yongan Bai; Xiangfeng Liu; Qingzhi Wang; Hai Chi; Zhiyuan Song; Jie Zheng (Food Chemistry, 2025)

Effects of radio frequency explosion puffing on the texture of purple sweet potato chips and the physicochemical properties of the flour under different energy inputs and pressures - Chao Mao; Li Zhang; Shijing Zhang; Zhi Chang; Pengfei Ye; Tianshuo Yan; Yequn Wang; Xiangwei Chen; Hongfei Fu; Yunyang Wang; Ke Wang (Food Chemistry, 2025)

An Improved Fractional Damage Creep Model for Shale and Its Application to the Long-term Fracture Conductivity Prediction - Jiale Fu; Shu Jiang; Linhao Zhang; Pengfei Xiong; Kai Zhang (Computers and Geotechnics, 2025)

Strain-engineered selenium vacancies in MoSe2 cocatalysts to redirect photocarrier trapping for efficient hydrogen evolution - Siyi Zhang; Ni Hu; Zhenfei Fu; Shilong Suo; Qing Han; Ziwu Han; Ziyue Zhang; Ruiling Zhang; Bing Jin; Zhenhua Zhang; Zhihong Lu; Pengfei Fang (Chemical Engineering Journal, 2025)

Structural and physicochemical characterization of plant-derived galactomannans: revealing promising substrates for mannooligosaccharides production - Shujun Hou; Yijin Zhang; Rui Yang; Wei Xu; Huanli Wang; Zhijin Zhang; Botao Liu; Guiyao Dai; Ting Wang; Pengfei Li; Liang He; Ke Wu; et al. (Carbohydrate Polymers, 2025)

Novel Parameter Calibration Method of WRF-Hydro in Ungauged Areas Combining Satellite-Based Soil Moisture and Multisource Meteorological Data - Qingzhi Zhao; Yatong Li; Hongwu Guo; Zufeng Li; Yibin Yao; Mingxian Hu; Pengfei Geng; Yuan Zhai; Xiaohua Fu; Qiong Wu (Water Resources Management, 2025)

Inhibition of physicochemical and structural alterations of gluten proteins by fructo-oligosaccharides on frozen mixed cereal dough - Yingnan Liu; Kaiwen Liu; Tianren Zhang; Pengfei Jiang; Libo Qi; Baoshang Fu; Shan Shang (Food Chemistry, 2025)

Remodeling and Characterization Analysis of Corticospinal Tract in Patients with Intracerebral Hemorrhage in the Basal Ganglia - Jun Zhang; Lichao Wei; Fengyuan Zhou; Zhuoyin Du; Meihua Wang; Gang Wu; Qiang Yuan; Caihua Xi; Weijian Yang; Pengfei Fu; Biwu Wu; Jian Yu; et al. (Translational Stroke Research, 2025)

Oleanane triterpenoids with PTP1B and α -glucosidase inhibitory activities from Caulophyllum robustum - Pengfei Jin; Jing Wang; Zhuyu Qin; Miao Fu; Binhua Qin; Xinqiao Liu (Natural Product Research, 2025)

Characterizing the capability of public DEMs for mapping global floodplain bathymetry - Yaling Lin; Chenyu Fan; Kai Liu; Lingyang Liu; Xinyuan Deng; Pengju Xu; Pengfei Zhan; Xuefei Fu; Chunqiao Song (Journal of Hydrology, 2025)

Linear-light regulated bidirectional electron transfer of a pyromellitic diimide-based photochromic coordination polymer for inkless and erasable printing and information anticounterfeiting - Jingfang Wang; Pengfei Hao; Shimin Zhang; Yi Xu; Jin Qin; Junju Shen; Yunlong Fu (Chemical Engineering Journal, 2025)

Development of a novel dual-emission probe for accurate detection and imaging of HClO in environmental and biological systems - Qi Li; Pengfei Qi; Luan Wang; Shuang Fu; Hongguang Zhang; Song Chen; Shuang Li; Chuan He; Peng Hou; Wenqiang Chen; Cuiyan Han (Journal of Hazardous Materials, 2025)

Modeling and energy-saving operation optimization of high-speed maglev trains - Chengcheng Fu; Pengfei Sun; Qingyuan Wang; Xiaoyun Feng (Journal of Cleaner Production, 2025)

Antibacterial mechanism of lysine against Escherichia coli O157:H7, its action on lettuce and in reducing the severity of murine colitis - Lei Tian; Luyao Ma; Yudong Tian; Ting Zhou; Chunling Zhang; Hu Pan; Yanna Dai; Jifeng Pu; Chengyu Fu; Pengfei Zhang; Xin Wang (Food Microbiology, 2025)

Evaluating the contribution of residential coal combustion to atmospheric nitrous acid (HONO) in winter - Yang Wang; Pengfei Liu; Chenglong Zhang; Chaoyang Xue; Xiaoxi Zhao; Shuang Fu; Zichen Wu; Yifei Song; Yuzheng Wang; Chengtang Liu; Yujing Mu (Environmental Pollution, 2025)

Enriched Krylov subspace method for resolving interferometric parameter block adjustment model in elevation calibration of spaceborne InSAR digital surface model - Liqun Liu; Haiqiang Fu; Chenglong Cao; Yifan Zhang; Kun Han; Xun Du; Pengfei Li; Jie Li; Zhiwei Li (Journal of Geodesy, 2025)

The SnRK1 kinase TaSnRK1.10 positively regulates heavy metal chromium tolerance mainly by mediating reactive oxygen species homeostasis and activating the phenylpropanoid biosynthetic pathway in wheat - Yihan Fu; Cong Chen; Pei Pei; Xiangyang Hao; Jiajia Jin; Shujie Shi; Qiang Ge; Pengfei Wang; Gezi Li; Guozhan Fu; Changqing Du; Guozhang Kang (Journal of Hazardous Materials, 2025)

Effects of dry heating and extrusion on physicochemical properties, in vitro digestibility and instant properties of rice, chickpea, and oat flour - Kaiwen Liu; Xiaolin Ao; Pengfei Jiang; Baoshang Fu; Libo Qi; Chengrong Wen; Shan Shang (Food Bioscience, 2025)

Highly stretchable, self-adhesive, conductive, and tough hydrogel reinforced with cellulose nanofibers for wearable biosensor and ultrasonic nanogenerator - Yijun Fu; Junyi Zou; Yijie Wang; Zhengyu Yao; Pengfei Lv; Dingsheng Wu; Qufu Wei; Wei Zhang; Yu Jiang; Dawei Li (Chemical Engineering Journal, 2025)

Nano-sized coordination polymer particles (CPPs) for synergetic application in antibacterial and anticancer therapeutics - Wang Ding; Tikai Zhang; Ruiying Fu; Chengtao Yu; Cheng Zhang; Kuaibing Wang; Pengfei Zhang (Chemical Engineering Journal, 2025)

Recent advancements in observations, sources, and environmental effects of atmospheric hydrogen peroxide (H2O2) - Lian Duan; Shuyuan Jia; Xuran Li; Yalong Wang; Yiming Zhang; Shuang Fu; Yang Wang; Can Ye; Pengfei Liu; Zongbo Shi; Yujing Mu (Atmospheric Environment, 2025)

Composite geopolymer based on copper tailings: Mechanical properties, strength models and microstructure - Wei Wang; Pengfei Wei; Ping Jiang; Na Li; Fuyong Chu; Jiajia Fu; Xudong Wang (Journal of Environmental Chemical Engineering, 2025)

Evaluation and selection of superior Fraxinus mandshurica families for genetic improvement using growth traits, morphological characteristics, and wood properties - Meng Fu; Ronghua Liang; Pengfei Wang; Qiang Feng; Chaoqun Li; Ying Xin; Yaguang Zhan; Fansuo Zeng (Euphytica, 2025)

Functional and taxonomic biogeographical patterns of carbon-cycling microbial communities in farmland ecosystems of Shaanxi Province, China - Pengfei Li; Zirong Kong; Yiwei Bai; Wenjiang Fu; Yulong Li; Qiao Guo; Hangxian Lai (Applied Soil Ecology, 2025)

Effects of 2-hydroxypropyl-β-cyclodextrin and 28-homobrassinolide on the physiological characteristics, gene expression and terpenoid indole alkaloid accumulation in Catharanthus roseus cambial meristematic cell cultures - Fangfang Fu; Haihua Li; Li Ling; Jiahe Li; Yifei Chen; Weijie Hu; Jiayu Li; Lin Ou; Zhaoxi Chen; Jun Li; Pengfei Zhou (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

Improving light use efficiency models via the introduction of both the diffuse fraction and radiation scalar - Pengfei Zhao; Guanghui Huang; Xufeng Wang; Zhen Zhang; Guojiang Wang; Ziyan Huang; Youjing Fu (Science of The Total Environment, 2025)

Study of association between embryo growth arrest (EGA) and atmospheric fine particulate matter pollution (PM2.5) and spatial metabolomics of villi derived from pregnant women - Lirong Bai; Pengfei Fu; Chuan Dong; Zhiping Li; Jianwei Yue; Xinling Li; Qi Cao; Yuankun Han; Shufen Zhang; Ruijin Li (Journal of Hazardous Materials, 2025)

Physicochemical and conformational changes of krill myofibrillar protein induced by two-stage thermal treatment and their relationship with muscle texture - Xiaofang Liu; Kaiwen Liu; Baoshang Fu; Pengfei Jiang; Libo Qi; Shan Shang (Food Chemistry, 2025)

Pi-efficient wheat cultivars screened by using both functional marker CAPS-799 and field experiment - Jinfeng Wang; Zedong Chen; Huanting Shi; Chuang Lou; Kaixia Fu; Yaxin Wang; Bo Yu; Tiancai Guo; Yonghua Wang; Pengfei Wang; Guozhang Kang (Field Crops Research, 2025)

Mechanisms of hydraulic erosion control in different microrelief patterns of loess sloped farmland under continuous rainfall - Xinkai Zhao; Xiaoyu Song; Danyang Wang; Lanjun Li; Pengfei Meng; Chong Fu; Long Wang; Wanyin Wei; Yu Liu; Huaiyou Li (CATENA, 2025)

A Python toolkit for integrating geographic information system into regulatory dispersion models for refined pollution modeling - Haobing Liu; Pengfei Gao; Sheng Xiang; Hong Zhu; Jia Chen; Qingyan Fu (Environmental Modelling & Software, 2025)

Multifunctional role of surfactant in fabricating polyamide nanofiltration membranes for Li+/Mg2+ separation - Shang Fang; Kecheng Guan; Aiwen Zhang; Liheng Dai; Siyu Zhou; Wenming Fu; Mengyang Hu; Ping Xu; Pengfei Zhang; Zhan Li; Zhaohuan Mai; Hideto Matsuyama (Desalination, 2025)

Mushroom polyphenol oxidase inactivation kinetics and structural changes during radiofrequency heating - Huiyun Pang; Yiming Jia; Zhi Zhang; Yingman Xie; Mingxia Song; Baozhong Cui; Pengfei Ye; Xiangwei Chen; Hongfei Fu; Yequn Wang; Yunyang Wang (Food Bioscience, 2024)

Biochar induced the decoupling of exciton dissociation and intersystem cross in BiOBr heterojunction for dual-channel boosted oxygen activation - Tian Fu; Hanbing Zhang; Linxing Wang; Tao Zhang; Jing Sun; Kun Liu; Luo Guo; Pengfei Wang; Sihui Zhan (Chemical Engineering Journal, 2024)

Three-dimensional CSAMT Forward Modeling of Potential Landslide Sliding Surfaces Using Finite Element Method - Ruo Wang; Qingyun Di; Da Lei; Changmin Fu; Pengfei Liang; Miaoyue Wang (Applied Geophysics, 2024)

Visible-light-induced radical difluoromethylation/cyclization of biarylvinyl azides: Facile access to CF2H-labelled phenanthridines - Guojie Yin; Jingjing Huang; Pengfei Hu; Weijun Fu (Journal of Fluorine Chemistry, 2024)

Progress in the application of novel cryoprotectants for the stabilization of myofibrillar proteins - Shan Shang; Yueyue Wang; Pengfei Jiang; Baoshang Fu; Xiuping Dong; Libo Qi (Critical Reviews in Food Science and Nutrition, 2024)

Characterization and immune role of class B scavenger receptor member 1 in spotted sea bass (Lateolabrax maculatus) - Yichen Fu; Chao Zhao; Changhong Lin; Bo Zhang; Lulu Yan; Bo Zhang; Pengfei Wang; Lihua Qiu (Fish & Shellfish Immunology, 2024)

Effect of exogenous protein substitution in glutinous rice cake: Batter rheology, structure, and retrogradation behavior - Yingnan Liu; Shulei Yu; Pengfei Jiang; Baoshang Fu; Libo Qi; Shan Shang (Journal of Cereal Science, 2024)

Lithospheric electrical structure and geodynamic model of the red river fault zone and its adjacent areas in southwest China: Constraints from 3-D magnetotelluric imaging - Zhe Yun; Zhiguo An; Qingyun Di; Yilang Zhang; Pengfei Liang; Changmin Fu (Journal of Asian Earth Sciences, 2024)

Effect of hot air-assisted radio frequency rotation heating system on improving heating uniformity of dried black fungus (Auricularia auricula) - Zheng Geng; Yingman Xie; Pengfei Ye; Yanan Sun; Hongfei Fu; Xiangwei Chen; Yequn Wang; Yunyang Wang (Food and Bioproducts Processing, 2024)

Relating the carbon sources to denitrifying community in full-scale wastewater treatment plants - Jinling Chen; Xia Tang; Xuewei Wu; Biping Li; Xia Tang; Xueran Lin; Pengfei Li; Hang Chen; Fu Huang; Xuhan Deng; Xiaojing Xie; Chaohai Wei; et al. (Chemosphere, 2024)

Ternary-coordination-regulated polyamide nanofiltration membranes for Li+/Mg2+ separation - Shang Fang; Kecheng Guan; Siyu Zhou; Qiangqiang Song; Yongxuan Shi; Wenming Fu; Zhan Li; Ping Xu; Mengyang Hu; Zhaohuan Mai; Pengfei Zhang; Hideto Matsuyama (Desalination, 2024)

Synergic effect of multi-frequency thermosonication and germinant on Alicyclobacillus acidoterrestris spore inactivation and underlying mechanisms - Yingman Xie; Huiyun Pang; Chao Mao; Pengfei Ye; Baozhong Cui; Xiangwei Chen; Hongfei Fu; Yequn Wang; Yunyang Wang (Food Bioscience, 2024)

Paleoclimatic application of spectral parameters to the eolian red clay of the Jianzha Basin, northeastern margin of the Tibetan Plateau - Chaofeng Fu; Ju’e Tian; Xinwen Xu; Yougui Song; Jun Zuo; Feng Wang; Lin Chen; Pengfei Li; Xiaoke Qiang (Science China Earth Sciences, 2024)

Predicting miRNA–Disease Associations by Combining Graph and Hypergraph Convolutional Network - Xujun Liang; Ming Guo; Longying Jiang; Ying Fu; Pengfei Zhang; Yongheng Chen (Interdisciplinary Sciences: Computational Life Sciences, 2024)

Algae-bacteria consortia promotes the cell growth of marine microalgae Phaeodactylum tricornutum and Chrysotila roscoffensis - Jiaqi Fang; Yan Sun; Zhujun Zhu; Jian Li; Pengfei Cheng; Spiros N. Agathos; Yuanyuan Fu; Lin Zhang; Chengxu Zhou; Jichang Han (Algal Research, 2024)

DPP8/9 inhibition attenuates the TGF-β1-induced excessive deposition of extracellular matrix (ECM) in human mesangial cells via Smad and Akt signaling pathways - Ke Li; Yuzhan Zhang; Weihao Zhao; Rongrong Wang; Yan Li; Linting Wei; Li Wang; Xianghui Chen; Zhao Chen; Pengfei Liu; Na Nie; Xuefei Tian; et al. (Toxicology Letters, 2024)

Assessment of the stabilization effect of ferrous sulfate for arsenic-contaminated soils based on chemical extraction methods and in vitro methods: Methodological differences and linkages - Ziqi Geng; Pengfei Wang; Naiyi Yin; Xiaolin Cai; Yaqi Fu; Chuanfang Fan; Xuhui Chang; Yunpeng Li; Jingnan Ma; Yanshan Cui; Peter E. Holm (Science of The Total Environment, 2024)

Freezing pre-treatment improves radio frequency explosion puffing (RFEP) quality by altering the cellular structure of purple sweet potato [Ipomoea batatas (L) Lam.] - Chao Mao; Yurui Chen; Tong Liu; Pengfei Ye; Yequn Wang; Xiangwei Chen; Hongfei Fu; Yunyang Wang; Ke Wang (Food Research International, 2024)

Radio frequency puffing of purple sweet potato nutritious snacks - Yingman Xie; Qiang Liu; Chao Mao; Huiyun Pang; Pengfei Ye; Baozhong Cui; Xiangwei Chen; Hongfei Fu; Yequn Wang; Yunyang Wang (Journal of Food Engineering, 2024)

Inhibition of protein denaturation and oxidation of prepared shrimp paste by sturgeon skin collagen peptide - Yueyue Wang; Xiaofang Liu; Pengfei Jiang; Libo Qi; Baoshang Fu; Shan Shang (Food Bioscience, 2024)

Selenium binding protein 1 protects renal tubular epithelial cells from ferroptosis by upregulating glutathione peroxidase 4 - Weihao Zhao; David J. Nikolic-Paterson; Ke Li; Yan Li; Yinhong Wang; Xianghui Chen; Zhaoyang Duan; Yuzhan Zhang; Pengfei Liu; Shemin Lu; Rongguo Fu; Lifang Tian (Chemico-Biological Interactions, 2024)

Occupational exposure to silica and risk of gastrointestinal cancers: a systematic review and meta-analysis of cohort studies - Jiyuan Shao; Pengfei Fu; Shengchun Wang; Hong Cheng; Xin Zhang (International Archives of Occupational and Environmental Health, 2024)

Role of keystone drives polycyclic aromatic hydrocarbons degradation and humification especially combined with aged contaminated soil in co-composting - Jiayue Huang; Ziwei Jiang; Anyang Li; Fangzhi Jiang; Pengfei Tang; Jizhe Cui; Wenxuan Feng; Chang Fu; Qian Lu (Journal of Environmental Management, 2024)

Comprehensive evaluation of thermally conductive functional layer on snow-melting performance for electric heating bridge system - Chaoliang Fu; Kai Liu; Wang Zhi; Pengfei Liu; Markus Oeser (Cold Regions Science and Technology, 2024)

Novel Ag-modified vanadate nanosheets for determination of small organic molecules with laser desorption ionization mass spectrometry - Yanli Zhu; Jikai Wang; Pengfei Zeng; Chengxiao Fu; Danjun Chen; Yuehua Jiang; Yiyang Sun; Zhulan Xie (Journal of Hazardous Materials, 2024)

Taking full advantage of ‘low-quality’ datasets in watershed modeling and management: From a perspective of parameter calibration - Yi Rong; Chengxin Qin; Haw Yen; Fu Sun; Pengfei Du; Siyu Zeng (Journal of Environmental Management, 2024)

Synthesis, crystal structures, and biological activity of aroylhydrazone di-m-chlorobenzyltin complexes - Wujiu Jiang; Pengfei Zhou; Le Chen; Weiwei Fu; Yuxing Tan (JBIC Journal of Biological Inorganic Chemistry, 2023)

Combination of radio frequency heating and antibacterial agents for microorganism control in the production of packaged tofu - Baozhong Cui; Ke Wang; Nan Hu; Yanan Sun; Chao Mao; Pengfei Ye; Huiyun Pang; Yequn Wang; Hongfei Fu; Xiangwei Chen; Yunyang Wang (Food Control, 2023)

Genome-Wide Identification of MYB Family Genes in Cerasus humilis Reveals Candidate Genes Involved in Flavonoid Biosynthesis - Xiaofang Xue; Hongbo Fu; Xiwen Guo; Jiancheng Zhang; Pengfei Wang; Xiaopeng Mu; Shuai Zhang; Junjie Du (Plant Molecular Biology Reporter, 2023)

The identification and expression of an interleukin-21 receptor in large yellow croaker (Larimichthys crocea) - Hanyu Wu; Qiuling Fu; Yan Teng; Pengfei Mu; Jingjie Chen; Xinhua Chen (Molecular Biology Reports, 2023)

Effects of foods and food components on the in vitro bioaccessibility of total arsenic and arsenic species from Hizikia fusiforme seaweed - Yaqi Fu; Huili Du; Pengfei Wang; Naiyi Yin; Xiaolin Cai; Ziqi Geng; Yunpeng Li; Yanshan Cui (Science of The Total Environment, 2023)

Significantly mitigating PM2.5 pollution level via reduction of NOx emission during wintertime - Shuang Fu; Pengfei Liu; Xiaowei He; Yifei Song; Junfeng Liu; Chenglong Zhang; Yujing Mu (Science of The Total Environment, 2023)

Geolocated social media data for measuring park visitation in Shenzhen, China - Langjiao Li; Qingyun Du; Fu Ren; Lei Huang; Mihai Voda; Pengfei Ning (Urban Forestry & Urban Greening, 2023)

Investigation on microscopic forces between methane hydrate particles in gas phase dominated system - Pengfei Li; Shikun Tong; Jihao Pei; Jianbo Zhang; Yukun Guo; Xiao Liu; Weiqi Fu; Zhiyuan Wang (Fuel, 2023)

Exploration of potential driving mechanisms of Comamonas testosteroni in polycyclic aromatic hydrocarbons degradation and remodelled bacterial community during co-composting - Fangzhi Jiang; Ziwei Jiang; Jiayue Huang; Pengfei Tang; Jizhe Cui; Wenxuan Feng; Chunjing Yu; Chang Fu; Qian Lu (Journal of Hazardous Materials, 2023)

Precursor Development of Sandstone Failure Using IR to Measure the Fractal Characteristics - Hai Sun; Hongyan Zhu; Changyan Shi; Fei Wang; Liqiang Ma; Chun Fu; Pengfei Cui; Yuanyuan Du (Geotechnical and Geological Engineering, 2023)

Experimental investigation on highly potent inhibitors of natural gas hydrate in oil-free flow system - Jihao Pei; Zhiyuan Wang; Pengfei Li; Junjie Hu; Shikun Tong; Jie Zhong; Peng Liu; Weiqi Fu (Fuel, 2023)

Ca–La layered double hydroxide (LDH) for selective and efficient removal of phosphate from wastewater - Yuhang Cao; Xuewei Wu; Biqing Li; Xia Tang; Xueran Lin; Pengfei Li; Hang Chen; Fu Huang; Chaohai Wei; Jian Wei; Guanglei Qiu (Chemosphere, 2023)

Abscisic acid alleviates mercury toxicity in wheat (Triticum aestivum L.) by promoting cell wall formation - Jinxi Wang; Jie Gao; Lanjie Zheng; Yihan Fu; Li Ji; Changyu Wang; Shasha Yuan; Jingyu Yang; Jin Liu; Gezi Li; Pengfei Wang; Yonghua Wang; et al. (Journal of Hazardous Materials, 2023)

Construction of bubbles enrichment sites and gas-diffusion-microchannel to assist Cr(VI) electrochemical reduction in a flow-through electrochemical system - Chen Peng; Zhang Xinwan; Meng Guangyuan; Fu Tao; Xue Yuanyuan; Wang Zhiwei; Song Pengfei; Zhang Lehua; Liu Haifeng (Chemical Engineering Journal, 2023)

Feeding Habit-Specific Heavy Metal Bioaccumulation and Health Risk Assessment of Fish in a Tropical Reservoir in Southern China - Di Wu; Hao Feng; Ying Zou; Juan Xiao; Pengfei Zhang; Yuxiang Ji; Sovan Lek; Zhiqiang Guo; Qiongyao Fu (Fishes, 2023)
Dietary uptake is well known as the predominant pathway of heavy metal bioaccumulation in organisms. Our study used a typical tropical reservoir and fish as a modeling system to test the hypothesis that feeding habits and living habitats significantly affect heavy metal bioaccumulation in fish. Specifically, Cr, Mn, Fe, Ni, Cu, Zn, Cd, and Pb concentrations in water, sediment, and fish, and δ13C and δ15N in 13 fish species were detected in the Songtao Reservoir of Hainan Province, southern China. Our results indicated that Zn concentration in carnivorous fish was higher than in omnivorous fish. Principal components analysis visually differentiated pelagic, benthopelagic, and demersal fish groups. Moreover, we found that the fish feeding in the demersal habitat showed higher heavy metal levels than those in the pelagic habitat. Additionally, the heavy metal contents in demersal fish were significantly positively correlated with sediments, while no positive correlation was observed in pelagic-feeding fish. The δ15N and the concentration of Ni, Zn in fish had a significantly positive correlation, suggesting the potential biomagnification. In contrast, Ni, Fe, Cu, and Cd negatively correlated with fish body weight/length, indicating the growth dilution effects. Finally, the estimated daily intake (EDI) of the metals was far below the provisional tolerable daily intake (PTDI), and target hazard quotients (THQ) were

Promotion and inhibition effects of wax on methane hydrate formation and dissociation in water-in-oil emulsions - Shikun Tong; Pengfei Li; Fengjun Lv; Zhiyuan Wang; Weiqi Fu; Jianbo Zhang; Litao Chen; Xuerui Wang (Fuel, 2023)

A two-step three dimensional marine magnetotelluric inversion method with considering rugged seafloor topography: Synthetic studies - Pengfei Liang; Qingyun Di; Changmin Fu; Ruo Wang; Qihui Zhen; Zhe Yun; Jiagang Zhang (Science China Earth Sciences, 2023)

An ultrasensitive FET biosensor based on vertically aligned MoS2 nanolayers with abundant surface active sites - Pengfei Song; Pengfei Ou; Yongjie Wang; Hang Yuan; Sixuan Duan; Longyan Chen; Hao Fu; Jun Song; Xinyu Liu (Analytica Chimica Acta, 2023)

Deep learning-assisted ultra-accurate smartphone testing of paper-based colorimetric ELISA assays - Sixuan Duan; Tianyu Cai; Jia Zhu; Xi Yang; Eng Gee Lim; Kaizhu Huang; Kai Hoettges; Quan Zhang; Hao Fu; Qiang Guo; Xinyu Liu; Zuming Yang; et al. (Analytica Chimica Acta, 2023)

Learning and inferring the diurnal variability of cyanobacterial blooms from high-frequency time-series satellite-based observations - Hu Li; Chengxin Qin; Weiqi He; Fu Sun; Pengfei Du (Harmful Algae, 2023)

Post-failure analysis of landslide blocking river using the two-phase double-point material point method: a case of western Hubei, China - Wenjie Du; Qian Sheng; Xiaodong Fu; Jian Chen; Pengfei Wei; Yongqiang Zhou (Bulletin of Engineering Geology and the Environment, 2023)

One-pot synthesis of ternary-emission molecularly imprinted fluorescence sensor based on metal–organic framework for visual detection of chloramphenicol - Xiaodan Wu; Sisi Tang; Pengfei Zhao; Kangling Tang; Yu Chen; Jinli Fu; Shu Zhou; ZhaoXia Yang; Zhaohui Zhang (Food Chemistry, 2023)

Evoking and enhancing ferroptosis of cancer stem cells by a liver-targeted and metal-organic framework-based drug delivery system inhibits the growth and lung metastasis of hepatocellular carcinoma - Pengfei Zhang; Junjie Fu; Jing Hu; Qingjun You; Xueyan Yao; Dong Hua; Jian Yin; Yong Mao (Chemical Engineering Journal, 2023)

A smartphone-assisted down/up-conversion dual-mode ratiometric fluorescence sensor for visual detection of mercury ions and l-penicillamine - Kangling Tang; Yu Chen; Sisi Tang; Xiaodan Wu; Pengfei Zhao; Jinli Fu; Huibin Lei; Zhaoxia Yang; Zhaohui Zhang (Science of The Total Environment, 2023)

Quinone redox cycling drives lignocellulose depolymerization and degradation in composting environments based on metagenomics analysis - Ru Sun; Ziyi Cao; Xiaoli Wen; Liangcai Ma; Yucheng Zhou; Jixuan Li; Mengxin Fu; Pengfei Zhu; Kecheng Li; Qunliang Li (Science of The Total Environment, 2023)

Functional analysis of a late embryogenesis abundant protein ZmNHL1 in maize under drought stress - Guorui Wang; Huihui Su; Salah Fatouh Abou-Elwafa; Pengyu Zhang; Liru Cao; Jiaxu Fu; Xiaowen Xie; Lixia Ku; Pengfei Wen; Tongchao Wang; Li Wei (Journal of Plant Physiology, 2023)

Random Noise Attenuation in Tunnel Based on EMD-T-FSS - Pengfei Zhou; Kai Li; Chao Fu; Xiaobin Xu; Zhijun Geng; Weimin Yang; Yi Zhang; Shuai Cao (Geotechnical and Geological Engineering, 2023)

Tea consumption and cerebral hemorrhage risk: a meta-analysis - Pengfei Cheng; Junxiang Zhang; Wenting Liu; Quan Sun; Zhaoxin Fu; Hao Lin; Sheng Bi; Jiaying Zhu (Acta Neurologica Belgica, 2022)

Genome-Wide Identification and Expression Analysis of AAAP Gene Family in Cerasus humilis During Fruit Development - Hongbo Fu; Pengfei Wang; Junjie Du; Xiaopeng Mu; Shengyong Yuan; Yongchao Yang; Jie Li (Plant Molecular Biology Reporter, 2022)

NPC1-regulated dynamic of clathrin-coated pits is essential for viral entry - Guoli Li; Bingqian Su; Pengfei Fu; Yilin Bai; Guangxu Ding; Dahua Li; Jiang Wang; Guoyu Yang; Beibei Chu (Science China Life Sciences, 2022)

Estrogen prevents cellular senescence and bone loss through Usp10-dependent p53 degradation in osteocytes and osteoblasts: the role of estrogen in bone cell senescence - Yu Wei; Jiayao Fu; Wenjing Wu; Pengfei Ma; Le Ren; Junhua Wu (Cell and Tissue Research, 2021)

Identification of Eltrombopag as a Repurposing Drug Against Staphylococcus epidermidis and its Biofilms - Juan Zhu; Pengfei She; Juhua Fu; Canhui Peng; Yong Wu (Current Microbiology, 2021)

The Combined Effects of Increased pCO2 and Warming on a Coastal Phytoplankton Assemblage: From Species Composition to Sinking Rate - Yuanyuan Feng; Fei Chai; Mark L. Wells; Yan Liao; Pengfei Li; Ting Cai; Ting Zhao; Feixue Fu; David A. Hutchins (Frontiers in Marine Science, 2021)
In addition to ocean acidification, a significant recent warming trend in Chinese coastal waters has received much attention. However, studies of the combined effects of warming and acidification on natural coastal phytoplankton assemblages here are scarce. We conducted a continuous incubation experiment with a natural spring phytoplankton assemblage collected from the Bohai Sea near Tianjin. Experimental treatments used a full factorial combination of temperature (7 and 11°C) and pCO 2 (400 and 800 ppm) treatments. Results suggest that changes in pCO 2 and temperature had both individual and interactive effects on phytoplankton species composition and elemental stoichiometry. Warming mainly favored the accumulation of picoplankton and dinoflagellate biomass. Increased pCO 2 significantly increased particulate organic carbon to particulate organic phosphorus (C:P) and particulate organic carbon to biogenic silica (C:BSi) ratios, and decreased total diatom abundance; in the meanwhile, higher pCO 2 significantly increased the ratio of centric to pennate diatom abundance. Warming and increased pCO 2 both greatly decreased the proportion of diatoms to dinoflagellates. The highest chlorophyll a biomass was observed in the high pCO 2 , high temperature phytoplankton assemblage, which also had the slowest sinking rate of all treatments. Overall, there were significant interactive effects of increased pCO 2 and warming on dinoflagellate abundance, pennate diatom abundance, diatom vs. dinoflagellates ratio and the centric vs. pennate ratio. These findings suggest that future ocean acidification and warming trends may individually and cumulatively affect coastal biogeochemistry and carbon fluxes through shifts in phytoplankton species composition and sinking rates.

Applied properties and life cycle assessment of flexible packaging lamination processes: a comparative study - Haowei He; Yabo Fu; Youzhong Zhao; Siqi Liu; Guangshen Zuo; Pengfei Guo; Wencai Xu (The International Journal of Life Cycle Assessment, 2021)

Lactobacillus rhamnosus JYLR-005 Prevents Thiram-Induced Tibial Dyschondroplasia by Enhancing Bone-Related Growth Performance in Chickens - Fang Liu; Anan Kong; Pengfei Fu; Qin-qin Cao; Kun-sheng Tao; Di-yi Liu; Xue-bing Wang; Zong-xi Tong; Mujeeb Ur Rehman; Shu-cheng Huang (Probiotics and Antimicrobial Proteins, 2021)

Protist Interactions and Seasonal Dynamics in the Coast of Yantai, Northern Yellow Sea of China as Revealed by Metabarcoding - Yingjun Fu; Pengfei Zheng; Xiaoli Zhang; Qianqian Zhang; Daode Ji (Journal of Ocean University of China, 2020)

Increased EZH2 Levels in Anterior Cingulate Cortex Microglia Aggravate Neuropathic Pain by Inhibiting Autophagy Following Brachial Plexus Avulsion in Rats - Xiang-Lei Meng; Pengfei Fu; Lin Wang; Xun Yang; Guanghui Hong; Xin Zhao; Jie Lao (Neuroscience Bulletin, 2020)

Conversion of organic carbon from decayed native and invasive plant litter in Jiuduansha wetland and its implications for SOC formation and sequestration - Jianfang Yan; Lei Wang; Yiu Fai Tsang; Liwei Qian; Xiaohua Fu; Ying Sun; Pengfei Wu (Journal of Soils and Sediments, 2020)

Microsatellite records for volume 11, issue 3 - Pengfei Hu; Hao-Xiang Liu; Ying Pan; Yan-Fu Qu; Xueqi Tian; Ke-Xin Wang; Yu-Heng Wei; Xue-Ping Wu; Xiumei Xing; Zhengyi Zhang; Pei Zhao; Yu-Tian Zhao; et al. (Conservation Genetics Resources, 2019)

Epigenetic Alterations of Wnt Signaling Pathways in Nasopharyngeal Carcinoma - Pengfei Liu; Lu Fu; Robert Z. Qi (Current Pharmacology Reports, 2018)

The Effect of Divalent Metal Ions and Recycle Ratio of UASB Reactor on the Formation of Anammox Granules and Its Treatment Performance - Jinxiang Fu; Mingjun Zhou; Jie Yun; Yang Su; Pengfei Yu; Ming Sun; Xinqi Ji (Water, Air, & Soil Pollution, 2017)

Bearing Capacity of the New Composite Foundation with Discrete Material-Concrete Compound Piles - Youlin Guo; Minghua Zhao; Guihai Fu; Yongsuo Li; Pengfei Yu (Geotechnical and Geological Engineering, 2017)

Efficiency of several leaching reagents on removal of Cu, Pb, Cd, and Zn from highly contaminated paddy soil - Ruili Gao; Pengfei Zhu; Guangguang Guo; Hongqing Hu; Jun Zhu; Qingling Fu (Environmental Science and Pollution Research, 2016)

Promotion of breast cancer cells MDA-MB-231 invasion by di(2-ethylhexyl)phthalate through matrix metalloproteinase-2/-9 overexpression - Shuya Zhang; Jiehua Ma; Ziyi Fu; Zhilei Zhang; Jian Cao; Lei Huang; Wenqu Li; Pengfei Xu; Xin Cao (Environmental Science and Pollution Research, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Mapping the bathymetry of shallow coastal water using single-frame fine-resolution optical remote sensing imagery - Jiran Li; Huaguo Zhang; Pengfei Hou; Bin Fu; Gang Zheng (Acta Oceanologica Sinica, 2016)

Direct interspecies electron transfer accelerates syntrophic oxidation of butyrate in paddy soil enrichments - Huijuan Li; Jiali Chang; Pengfei Liu; Li Fu; Dewen Ding; Yahai Lu (Environmental Microbiology, 2015)
Summary Syntrophic interaction occurs during anaerobic fermentation of organic substances forming methane as the final product. H 2 and formate are known to serve as the electron carriers in this process. Recently, it has been shown that direct interspecies electron transfer ( DIET ) occurs for syntrophic CH 4 production from ethanol and acetate. Here, we constructed paddy soil enrichments to determine the involvement of DIET in syntrophic butyrate oxidation and CH 4 production. The results showed that CH 4 production was significantly accelerated in the presence of nano Fe 3 O 4 in all continuous transfers. This acceleration increased with the increase of nano Fe 3 O 4 concentration but was dismissed when Fe 3 O 4 was coated with silica that insulated the mineral from electrical conduction. Nano Fe 3 O 4 particles were found closely attached to the cell surfaces of different morphology, thus bridging cell connections. Molecular approaches, including DNA ‐based stable isotope probing, revealed that the bacterial S yntrophomonadaceae and G eobacteraceae , and the archaeal M ethanosarcinaceae , M ethanocellales and M ethanobacteriales , were involved in the syntrophic butyrate oxidation and CH 4 production. Among them, the growth of G eobacteraceae strictly relied on the presence of nano Fe 3 O 4 and its electrical conductivity in particular. Other organisms, except M ethanobacteriales , were present in enrichments regardless of nano Fe 3 O 4 amendment. Collectively, our study demonstrated that the nano Fe 3 O 4 ‐facilitated DIET occurred in syntrophic CH 4 production from butyrate, and G eobacter species played the key role in this process in the paddy soil enrichments.

Phagocytosis of Microglia in the Central Nervous System Diseases - Ruying Fu; Qingyu Shen; Pengfei Xu; Jin Jun Luo; Yamei Tang (Molecular Neurobiology, 2014)